Thermoelectric Properties of Bi2Te3/Sb2Te3 Thin Films - Gonçalves, L. M. (2005)
This presentation reports the deposition and characterization of n-type Bi2Te3 and p-type Sb2Te3 semiconductor films by thermal co-evaporation method. Power factors of 4.6×10-3 Wm-1K-2 and 1.3×10-3 Wm-1K-2, were measured at room temperature on n-type and p-type films, respectively.